Aspects of protection and social vulnerability of teenagers in public all-day schools - Laurena Moreira Pires; Márcia Maria de Souza; Marcelo Medeiros (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: identify and analyze aspects related to social vulnerability of a group of teenagers of a public all-day school with regard to harmful and abusive use of psychoactive drugs. Methods: a strategic social study, with a qualitative approach, was carried out with 49 teenagers of a public all-day secondary school. Focus groups were carried out between 2016 and 2017, and the resulting material was transcribed and analyzed by means of thematic content analysis, resulting in the following categories: The family I come from; Birds of a feather; If I'm studying, how can I work?; Drugs: a non-parallel universe. Results: social vulnerability was associated with unequal income distribution, fragile social relations affected by the harmful use of drugs and vulnerability of public all-day schools. Final considerations: all-day schools did not appear as an effective tool to break away with the context of social vulnerability regarding the use of drugs.